A Comprehensive Analysis of the Thrombin Binding Aptamer Containing Functionalized Pyrrolo-2'-deoxycytidines - Weronika Kotkowiak; Zofia Jahnz-Wechmann; Anna Pasternak (MDPI AG, 2021)
Aptamers constitute an answer for the growing need for targeted therapy development. One of the most well-known representatives of this group of compounds is thrombin binding aptamers (TBA) targeted towards thrombin. The TBA inhibitory activity is determined by its spatial arrangement, which consists of two G-tetrads linked by two shorter TT loops and one longer TGT loop and folds into a unimolecular, antiparallel G-quadruplex structure. Interesting properties of the aptamer can be further improved via the introduction of a number of chemical modifications. Herein, a comprehensive analysis of the influence of pyrrolo-2'-deoxycytidine (Py-dC) and its derivatives on TBA physicochemical and biological properties has been presented. The studies have shown that the presence of modified residues at the T7 position of the TGT loop has only minor effects on TBA thermodynamic stability without affecting its folding topology. All analyzed oligomers exhibit anticoagulant properties, but only aptamer modified with a decyl derivative of Py-dC was able to inhibit thrombin activity more efficiently than unmodified, parental compounds. Importantly, the same compound also possessed the potential to effectively restrain HeLa cell line growth.